UPAYA MENINGKATKAN KINERJA GURU DALAM ADMINISTRASI PEMBELAJARAN MELALUI WORKSHOP PADA SUPERVISI AKADEMIK DI MTs NEGERI BATANG - MINARSIH MINARSIH (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2021)
Teacher performance was a process in determining the achievement of the school's vision and mission. Operational activities were one of the most basic performances in schools. It required teachers' skills in their fields or professionals. The researcher chose MTs Negeri Batang as the object of research. These indicated an unfavorable working situation. These could show how important the role of madrasah principals is in improving teacher performance in the quality learning process, especially in administration. Application of academic supervision with workshop techniques can increase active learning by arranging learning administration. The focus of this research will be more to know the extent of teacher performance and also in learning administration at MTs Negeri Batang. This research uses Madrasah Action Research as a method. After proceeding in several cycles in data collection, the researchers found teachers who showed seriousness in understanding and compiling teaching administration which was origin 79.6% especially after receiving teaching administration development guidance from researchers so that there was a 98.1% increase in the average in the preparation of teaching administration by 18.5%. It could be proven from the results of observations of the quality of quasi-learning administration. These showed that there was an increase in teacher competence from cycle 1, scores 81 there are 4 people from 36 (11.2%) to cycle 2 who scores 81 there are 35 of 36 teachers (97.2%) so that there is an increase in the quality of administration learning by 86%. ABSTRAKKinerja guru merupakan sebuah proses dalam menentukan proses ketercapaian visi dan misi sekolah. Kegiatan operasional merupakan salah satu kinerja yang paling pokok di sekolah dalam pembelajaran. Hal ini tentunya memerlukan tenaga guru yang terampil dalam bidangnya atau profesional. Peneliti memilih MTs Negeri Batang sebagai obyek penelitian. Hal ini menunjukkan adanya situasi kerja yang kurang baik. Hal ini terlihat betapa penting peran kepala madrasah dalam meningkatkan kinerja guru dalam proses pembelajaran yang bermutu terutama pada administrasi. Penerapan supervisi akademik dengan teknik workshop dapat meningkatkan pembelajaran aktif dengan menyusun administrasi pembelajaran. Selanjutnya, fokus dari penelitian ini akan lebih kepada mengetahui sejauh mana kinerja guru dalam administrasi pembelajaran di MTs Negeri Batang. Penelitian ini menggunakan Penelitian Tindakan Madrasah sebagai metode. Setelah berproses dalam beberapa siklus dalam pengambilan data, peneliti menemukan guru yang menunjukkan keseriusan dalam memahami dan menyusun administrasi mengajar yang semula 79,6% apalagi setelah mendapatkan bimbingan pengembangan administrasi mengajar dari peneliti sehingga terjadinya 98,1% peningkatan rata-rata dalam penyusunan administrasi mengajar sebesar 18,5%. Hal itu juga dapat dibuktikan dari hasil observasi kualitas administrasi pembelajaranan semu memperlihatkan bahwa terjadi peningkatan kompetensi guru dari siklus 1 yang memperoleh nilai ? 81 ada 4 orangdari 36 (11,2%) ke siklus 2 yang memperoleh nilai ? 81 ada 35 dari 36 guru (97,2%) sehingga terjadinya peningkatan dalam kualitas administrasi pembelajaran sebesar 86%.